From Exile to Affirmation: The Poetry of Joseph Brodsky - David Patterson (Studies in 20th & 21st Century Literature, 1993)
This article examines the relation between the exile of the poet from his homeland and the "exile of the word." The notion of the exile of the word pertains to the poet's problem of re-introducing meaning to the word—an excess of meaning that conveys more than the word can normally convey—through his poetry. Showing how the poet in exile becomes a poet of exile, the article examines what poetry has to do with a larger difficulty of exile and homelessness in human life. Brodsky's poetry, the article argues, addresses this very difficulty. The article concludes that the human capacity to dwell in the world is a capacity to instill the word with meaning, and that this is one important message to come to us through the poetry of Joseph Brodsky.
Keywords: poetry; Russian poetry; American poetry; Joseph Brodsky; exile; homeland; meaning; identity; homelessness